Real‐time in vivo dosimetry for SBRT prostate treatment using plastic scintillating dosimetry embedded in a rectal balloon: a case study. (8th November 2016) - Cantley, Justin L.; Cheng, Chee‐Wai; Jesseph, Fredrick B.; Podder, Tarun K.; Colussi, Valdir C.; Traughber, Bryan J.; Ponsky, Lee E.; Ellis, Rodney J.
Abstract : A novel FDA approved in vivo dosimetry device system using plastic scintillating detectors placed in an endorectal balloon to provide real‐time in vivo dosimetry for prostatic rectal interface was tested for use with stereotactic body radiotherapy (SBRT). The system was used for the first time ever to measure dose during linear accelerator based SBRT. A single patient was treated with a total dose of 36.25 Gy given in 5 fractions. Delivered dose was measured for each treatment with the detectors placed against the anterior rectal wall near the prostate rectal interface. Measured doses showed varying degrees of agreement with computed/ planned doses, with average combined dose found to be within 6% of the expected dose. The variance between measurements is most likely due to uncertainty of the detector location, as well as variation in the placement of a new balloon prior to each fraction. Distance to agreement for the detectors was generally found to be within a few millimeters, which also suggested that the differences in measured and calculated doses were due to positional uncertainty of the detectors during the SBRT, which had sharp dose falloff near the penumbra along the rectal wall. Overall, the use of a real time in vivo dosimeter provided a level of safety and improved confidence in treatment delivery. We are evaluating the device further in an IRB‐approved prospective partial prostate SBRT trial, and believe further clinical investigations are warranted. PACS number(s): 87.53.Bn, 87.53.Ly, 87.55.km